The Effectiveness of RME Approach to Elementary School Students' Mathematical Abilities: A Meta-Analysis Study - Samritin (Universitas Pendidikan Ganesha, 2023)
Various studies examining the effectiveness of the RME approach to the mathematics abilities of elementary school students have yielded inconsistent results. Therefore, this study aims to analyze the effectiveness of the RME approach to the mathematics abilities of elementary school students by using a type of meta-analysis research approach. This meta-analytic study analyzed 10 primary studies published in the last ten years. Data collection uses Google Scholar, ERIC, DOAJ, Springer, AIP Proceedings, IOP Sciences, and Elsevier databases. The results of the analysis show that the application of the RME approach has an effect on the mathematics abilities of elementary school students when compared to traditional learning (g = 0.63; p <0.01). The results of the moderator variable analysis showed that the effect of applying the RME approach to the mathematics abilities of elementary school students differed significantly based on class level (Qb = 6.01; p = 0.01) and sample size (Qb = 7.63; p = 0.01). However, there was no significant difference by year of study group (Qb = 3.16; p = 0.08) and type of publication (Qb = 2.58; p = 0.11). These findings are expected to be the basis for selecting strategies for learning mathematics in elementary schools so that the quality of learning can be improved.